Respuesta :

Part 1)

The slope-intercept form of the line equation

[tex]y = mx+b[/tex]

where m is the slope and b is the y-intercept

Given the equation

[tex]y = 3x-4[/tex]

comparing with the slope-intercept form of the line equation y = 3x-4

Thus, the slope of the line: m = 3

We know that the parallel lines have the same slopes.

Thus, the slope of the paralellel line is also: 3

substituting the slope m = 3 and the point (5, -3) in the slope-intercept form

[tex]y = mx+b[/tex]

-3 = 3(5) + b

-3 = 15 + b

b = -3-15

b = -18

Therefore, the value of y-intercept b = -18

now substituting the slope m = 3 and the y-intercept b = -18 in the slope-intercept form

[tex]y = mx+b[/tex]

y = 3x + (-18)

y = 3x - 18

Therefore, the equation of line parallel to the given line [tex]y = 3x-4[/tex] will be:

[tex]y = 3x - 18[/tex]

Part 2)

The slope-intercept form of the line equation

[tex]y = mx+b[/tex]

where m is the slope and b is the y-intercept

Given the equation

[tex]y = 3x-4[/tex]

comparing with the slope-intercept form of the line equation y = 3x-4

Thus, the slope of the line: m = 3

We know that a line perpendicular to another line contains a slope that is the negative reciprocal of the slope of the other line, such as:  

slope = m = 3

Thus, the slope of the the new perpendicular line = – 1/m = -1/3 = -1/3

substituting m = -1/3 and the point   (5, -3)  in the slope-intercept form

[tex]y = mx+b[/tex]

[tex]-3\:=\:-\frac{1}{3}\left(5\right)+b[/tex]

[tex]-\frac{5}{3}+b=-3[/tex]

[tex]b=-\frac{4}{3}[/tex]

now substituting the slope m = -1/3 and the y-intercept b = -4/3 in the slope-intercept form

[tex]y = mx+b[/tex]

[tex]y=\:-\frac{1}{3}x+\left(-\frac{4}{3}\right)[/tex]

[tex]y=\:-\frac{1}{3}x-\frac{4}{3}[/tex]

Therefore, the equation of the line perpendicular to the given line will be:

  • [tex]y=\:-\frac{1}{3}x-\frac{4}{3}[/tex]
ACCESS MORE